Emerging Afrikan Survivals : an Afrocentric Critical Theory. - Kamau, Kemayo (Studies in African American history and culture., 2003)
This work sets forth the guidelines for an Afrocentric literary theory and applies that theory to three novels: Invisible Man, Song of Solomon and The Chaneysville Incident.